Quantum dot-based thermometry uncovers decreased myosin efficiency in an experimental intensive care unit model - Li, Meishan; Cacciani, Nicola; Ribeiro, Fernando; Hedström, Yvette; Jena, Bhanu P.; Larsson, Lars (Frontiers in Physiology, 2024)
Critical illness myopathy (CIM) detrimentally affects muscle function in ICU patients, with a dramatic loss of muscle mass and function where the loss in specific force exceeds the loss in muscle mass (maximum force normalized to muscle cross-sectional area). The preferential loss of the molecular motor protein myosin, representing the hallmark of CIM, exhibiting a significant negative impact on the specific force generation by the muscle. Interestingly however, the preferential myosin loss is a relatively late event, and a specific loss in force generation capacity, is observed prior to the myosin loss. In the current study, employing an optimized cadmium telluride quantum dots (QD) mediated-thermometry approach to assess the efficiency of the myosin, we were able to determine the loss in specific force generated by the muscle, prior to the preferential loss of myosin. Reduction in QD fluorescent intensity correlates with greater heat loss, reflecting inefficient myosin function (less mechanical work performed and more heat loss on ATP hydrolysis by myosin). A significant decrease in myosin efficiency was observed in rats subjected to the ICU condition (immobilization and mechanical ventilation) for 5 days using an established experimental ICU model not limited by early mortality. Thus, qualitative myosin changes preceding quantitative myosin loss offer a mechanism underlying the early loss in specific force generation capacity associated with CIM and opens a venue for future CIM intervention strategies.